The impacts of natural disasters on Asian economies: Case studies of earthquakes and tsunamis in Japan, and storms and floods in Vietnam - Huong, Vu Thanh; Minh, Nguyen Hue (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 27 No 5E, 2023)
This paper examines the impacts of natural disasters on Asian economies through two cases of natural disasters in Japan and Vietnam. The paper uses published statistics and the opinions of experts together with personal analysis to examine these two cases, focusses on discussing the impacts of natural disaster on the economy of these two countries, and then expands conclusions to the scope of other Asian economies. The paper argues that natural disasters have considerable consequences on human life and economies, and lead to long term damage in Asia. The paper concludes by inferring some policy implications to help Asian countries minimize the impacts of natural disasters on their economies. It is emphasized that individual nations should understand the importance of nature and collaborate closely to protect nature and minimize the impact of disasters.